49 Identification of kallikrein-related peptidase 6 in primary mucosal malignant melanoma of the head and neck. Issue 5 (May 2015) - Thierauf, J.; Veit, J.; Knopf, A.; Bergmann, C.; Hoffmann, T.K.; Plinkert, P.K.; Koffler, J.; Heß, J.
Abstract : Introduction: Mucosal melanomas of the head and neck region are rare, aggressive tumors with a poor prognosis. The standard treatment is radical tumor resection, classical chemotherapies in advanced disease have shown little benefit. Kallikrein-related peptidase 6 (KLK6) belongs to a large family of peptidases, representing secreted chymotrypsin- and trypsin-like serine proteases with diverse expression under physiological and pathological conditions, including common types of human cancer. However, detailed immunohistochemical analyses on skin melanoma tissue sections revealed that KLK6 levels are not elevated due to cellular expression, but rather due to its expression in adjacent keratinocytes and endothelial cells within the tumor microenvironment. The aim of this study is to further classify mucosal melanomas molecularly with regard to KLK6 and to identify new possible targets or biomarkers. Material and methods: In cooperation with the Departments of Otorhinolaryngology at Technical Medical Center Munich and Essen, we were able to identify 22 patients with mucosal melanoma, medical history, tumor stage and paraffin-embedded tissue was available. Immunohistochemical staining with Kallikrein-related peptidase 6 was done, the results were correlated to the clinical data and course. Results: Tumors were located endonasally, within the nasal sinuses and the eyes in 10/22, 10/22 and 2/22. All patients had undergone surgery; in 34% of the cases adjuvant radiation was administered and 14% were given systemic interferon-therapy. The probability of one-year-survival was 81.8% (18/22) and of five-year-survival 50% (5/10). The mean overall-survival was 51 months, the mean recurrence-free-survival 26 months. Immunohistochemical analyses resulted in an expression of KLK6 in 72.7% of the analyzed cases. Cutaneous melanoma samples examined as reference showed weak staining in 33%. Additional to the cytoplasmatic staining in mucosal melanoma, nuclear staining was observed in 6 cases. Cross table analysis revealed that low or no KLK6 expression was significantly correlated with local tumor recurrence. Conclusion: The investigated Kallikrein-related peptidase 6 shows high expression in mucosal melanoma and – in contrast to most other human malignancies where KLK6 has been described before – a significant correlation of high KLK6 expression and low risk of local tumor recurrence.